Analysis of Instructional Materials in Arabic Language Student Worksheets (LKS) from the Perspective of Constructivist Theory at Dar al-Ma’mur Institute, Baso - Larasia, Reizka; Zubaidah, Zubaidah ((الطموحات ) EL-THUMUHAT, 2026)
Abstract This study aims to analyze the extent to which the content of the Arabic language Student Worksheets (LKS) aligns with constructivist learning theory at Dar al-Ma’mur Institute, Baso. The research employed a qualitative descriptive approach using content analysis of the eleventh-grade LKS based on constructivist theory indicators. Data were collected through document analysis, semi-structured interviews with Arabic language teachers, classroom observations, and supporting documents. The findings indicate that, in general, the worksheets are consistent with the core principles of constructivist theory, particularly in terms of active student engagement, the use of real-life contexts, and the connection of content to learners’ experiences. Topics such as health, travel, and shopping contribute to meaningful learning through interaction and task-based activities. However, several shortcomings were identified, including the absence of scaffolding stages, limited opportunities for student self-reflection, and weak elements of collaborative learning. In addition, the unit of analysis in this study remains limited, as the analysis focused only on the surface-level content without delving into the cognitive structure and interactive dimensions of the activities. The analytical methodology also requires strengthening through the use of more rigorous analytical tools and clearly defined, measurable evaluation criteria. A lack of critical depth in discussing the findings was also observed, which reduces the strength of the scientific conclusions. From a theoretical perspective, the study’s contribution remains limited, as it does not develop a new conceptual framework or adapt constructivist indicators to the specific context of Arabic language instruction. Furthermore, the research does not include empirical data measuring the impact of LKS use on student learning outcomes in a quantitative or quasi-experimental manner. Accordingly, while this study has the potential to serve as a strong evaluative research, it requires methodological reinforcement and deeper analysis to meet the standards of reputable peer-reviewed academic journals. Enhancing aspects related to collaborative learning, role-playing, group projects, and self-reflection tools, along with strengthening the methodological framework, would improve the effectiveness of Arabic language learning and address the needs of twenty-first-century learners. This study represents an initial step toward developing LKS and designing a more comprehensive constructivist-based Arabic language curriculum. Keywords: Constructivist theory, student worksheets, content analysis, Arabic language teaching.